Disease severity and trigger factors in Danish children with atopic dermatitis: a nationwide study. (23rd November 2020) - Gerner, T.; Haugaard, J.H.; Vestergaard, C.; Deleuran, M.; Jemec, G.B.; Mortz, C.G.; Agner, T.; Egeberg, A.; Skov, L.; Thyssen, J.P.
Abstract: Background: Atopic dermatitis (AD) is a prevalent chronically relapsing inflammatory skin disease of childhood. However, little is known about self‐reported trigger factors, impact on daily life and factors associated with AD severity. Methods: A nationwide questionnaire study of children in Denmark with hospital‐diagnosed AD in the time period 2014–2018. The web‐based questionnaire was completed by the legal parents. AD severity was assessed using Patient‐Oriented Eczema Measure (POEM) tool. Results: Of 3438 invited parents, 1343 (39%) completed the questionnaire. Factors associated with severe AD were onset during the first 6 months of life, onset of AD on multiple body regions, a history of hay fever, female sex and low maternal educational level. Staying home from daycare or school due to AD, concentration problems and sleep disturbances in the child were more frequently reported by parents to children with severe AD. Overall, 90% reported at least one AD trigger factor, and all were more frequently reported in children with severe AD. The three most commonly reported trigger factors were cold weather (51.9%), chlorinated water (35.7%) and warm weather (30.2%). Conclusions: We identified factors associated with severe AD in childhood, the impact on daily life, as well as the most common self‐reported triggers of AD. These findings may be valuable in clinical practice to inform about prognosis and educate families about trigger avoidance.